Ensaios contínuos de penetração de cone na argila cinza mole do Rio de Janeiro - Borges Neto, Camilo (1981)
This thesis commences by presenting a summary of the geotechnical characteristics of the Rio de Janeiro soft gray clay from the region of the Sarapuí River, as determined during recent investigations sponsored by the Instituto de Pesquisas Rodoviárias, IPR-DNER (Highways Research Institute of the National Road Department). A brief description is made of the Cone Penetration Test, the various types of conical tips used around the world, the applications of the test and the way its results can be analysed, providing geotechnical parameters of cohesive soils for design criteria. Following chapters deal with the test equipment used in the cone penetration tests on Sarapuí's clay deposit in the surroundings of the Washington Luiz Highway, emphasis being given to the conical tip designed and developed by the Author, provided with an electrical pressure transducer. After the description of the calibration procedures a discussion is made on reliability of the readings with the aid of statistical methods. Then, the thesis is focused on the field tests, the adopted procedures, the methods for calculation and interpretation of the data. The Cone Factor "Nk" is calculated with basis on the Bearing Capacity Theory and the results of Field Vane and Triaxial CIU-C (Shansep) Tests, obtained by other authors with the soil of same test site. Comparisons of "Nk" values are made with those obtained by other authors with soils of similar geotechnical characteristics. Finally, conclusions are presented both with respect to the new equipment and the tested soil, and some sugestions and recommendations are made for the improvement of the conical tip, aiming at decreasing the scattering of the curve and mainly, the temperature influence.